2015
DOI: 10.4103/0970-9290.159156
|View full text |Cite
|
Sign up to set email alerts
|

"Comparative evaluation of surface modified elastomeric ligatures for microbial colonization": An in vivo study

Abstract: Technological modifications of the elastomers using the Metafasix or OrthoShield Technology, is a definite improvement over the regular elastomers with regard to adhesion of S. mutans and Lactobacilli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Less surface degradation of superslick rings in oral environment and greater stress concentration of non-coated elastomeric ligatures has also been reported ( 30 ). Our findings are consistent with the earlier findings in this regard ( 5 , 15 ).…”
Section: Discussionsupporting
confidence: 94%
“…Less surface degradation of superslick rings in oral environment and greater stress concentration of non-coated elastomeric ligatures has also been reported ( 30 ). Our findings are consistent with the earlier findings in this regard ( 5 , 15 ).…”
Section: Discussionsupporting
confidence: 94%
“…Orthodontic elastomeric modules (OEM) are synthetic elastics made of polyurethane material, with advantages such as quickness of application, patient comfort and less expensive than self-ligation clips [ 12 ]. Apart from its practical benefits, it is evident from the literature review that elastomeric ligatures exhibit a greater number of microorganisms in the plaque around the brackets when compared with steel ligatures [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Bai et al found these technological modifications of the elastomers are a definite improvement over the regular elastomers with regard to adhesion of S. Mutans and Lactobacilli [ 13 ]. Caccianiga et al conclude that Orthoshield Safe-T-Tie ligatures reduce gingival inflammation and periodontal pathogens in orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to self-ligating brackets, the application of elastomeric ligatures is more popular due to lower costs, patient comfort, simplicity, and ease of use [ 15 ]. Studies have shown that the surface of elastomeric ligatures is more prone to bacterial plaque and accumulates a greater number of microorganisms in comparison with stainless-steel ligatures [ 16 ]. To reduce the risk of enamel decalcification and overcome the above-mentioned non-adherence by the patients, it has been suggested to coat the elastomeric ligatures with antimicrobial materials to provide a sustained and adequate dose of antibacterial delivery.…”
Section: Introductionmentioning
confidence: 99%